MENINGKATKAN KEGIATAN DAN HASIL BELAJAR BIOLOGI MELALUI METODE PEMBELAJARAN SISWA KELAS KOPERASI TIPE STAD - Lumban Tobing, Lindsa Elvina; Saragih, Siti Zahara; Mahriani, Rena (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2024)
The activities and learning outcomes of Class To overcome this problem, the STAD Type Cooperative Approach is used. To test the effectiveness of this learning model in order to improve student activity and learning outcomes, a classroom action research procedure was carried out, which was carried out over two cycles. Each cycle takes the following four stages: (1) planning, (2) implementation, (3) observation, and (4) reflection. Through various data collection techniques and instruments, research results were obtained. Then a discussion is carried out based on the techniques that have been determined. Finally, a conclusion was obtained to answer the main research problem as follows, Steps for using the STAD Type Cooperative Approach to improve the activities and learning outcomes of Class plan, (3) evaluate students' abilities in meeting each learning demand, and (4) follow up on the results carefull, The increase in student activity and learning outcomes in Biology lessons regarding the teaching material Patterns of Heredity after using the STAD Type Cooperative Approach, occurred in stages, such as actively asking questions, providing answers (responses) to questions from the teacher or other groups, being active in group discussions, preparing presentation materials group, willing to present the results of the discussion, and draw conclusions from the results of the discussion. The use of the STAD Type Cooperative Approach in Biology lessons regarding the teaching material Patterns of Heredity has been proven to increase the activity and learning outcomes of Class XII Science students at SMAS Methodist Rantauprapat.